The Rational Design and Biological Mechanisms of Nanoradiosensitizers - Hainan Sun; Xiaoling Wang; Shumei Zhai (Nanomaterials, 2020)
Radiotherapy (RT) has been widely used for cancer treatment. However, the intrinsic drawbacks of RT, such as radiotoxicity in normal tissues and tumor radioresistance, promoted the development of radiosensitizers. To date, various kinds of nanoparticles have been found to act as radiosensitizers in cancer radiotherapy. This review focuses on the current state of nanoradiosensitizers, especially the related biological mechanisms, and the key design strategies for generating nanoradiosensitizers. The regulation of oxidative stress, DNA damage, the cell cycle, autophagy and apoptosis by nanoradiosensitizers in vitro and in vivo is highlighted, which may guide the rational design of therapeutics for tumor radiosensitization.